The Role of Sekolah Penggerak in the Implementation of the Early Childhood Education Curriculum: A Literature Review - Rozalina, Fifi Alenda; Yufiarti, Yufiarti; Sri Wulan (proceedings.icesy, 2026)
The implementation of the Independent Curriculum at the Early Childhood Education (PAUD) level requires the role of educational units that will be the drivers of change in learning practices. This driving school program is presented as a policy that supports education, including at the PAUD level. This study aims to examine the role of sekolah penggerak in the implementation of the PAUD curriculum through a literature review. The research method used is a literature study by reviewing various sources in the form of scientific articles, books, policy documents relevant to the topic of sekolah penggerak and the PAUD curriculum. The results and discussion indicate that sekolah penggerak play a significant role in strengthening child-centered learning, improving educator competency, strengthening principal leadership, and implementing the PAUD Pancasila Student Profile (P5) strengthening project. Suggestions for further in-depth study should be carried out using field studies to obtain a more complete picture of the role of teachers in implementing the PAUD curriculum and to identify any obstacles teachers face in implementing the curriculum.